Pemanfaatan Situs Keagamaan (Internet) Sebagai Sumber Belajar PAO di SMPN Maur Kabupaten Musi Rawas Utara - Herlinah Herlinah (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
The problem raised in this study is how to use the facilities of religious sites (internet) as a source of learning for students of Islamic Religious Education by students of Maur State Junior High School, Rupit District, Musi Rawas Utara Regency and what are the inhibiting factors faced by students in using the site religion (internet) as one of the learning resources for Islamic Religious Education by students of Maur State Junior High School, Rupit District, Musi Rawas Utara Regency. To answer the above problems, the writer uses field research with an approach. The results showed that the use of the internet in learning Islamic Religious Education at Mauritian Junior High School, Rupit District, Musi Rawas Utara District was quite supportive in improving the quality of teaching and learning activities in the classroom, although there were obstacles faced by students in using religious sites (internet) as one a learning resource for Islamic Religious Education by students of Maur State Junior High School, Rupit District, Musi Rawas Utara District.